Manajemen MGMP untuk Peningkatan Kompetensi Profesional Guru Al Qur’an Hadist dalam Pembuatan Karya Tulis Ilmiah - Hanapiah, Ipan Rahayu; Sauri, Sopyan; Hanafiah, Nanang (Edukasi: Journal of Educational Research, 2021)
This research is motivated by the situation of teachers who are still constrained to improve their professional competence in making scientific papers, teachers are still focused on the mission of education and teaching in the classroom, while the vision and mission of scientific writing and scientific publications are often ignored, the implication is that the professional competence of teachers in writing and worrisome publication. The purpose of this study is to analyze the planning, implementation, evaluation, and to find out the constraints and solutions, MGMP management for improving the professional competence of Al Qur'an Hadith teachers in making scientific papers at State MTs in Majalengka Regency. The theological basis of this research is the concept of management which states that the essence of management is al-tadbir (regulation) which is a derivation of the word dabbara (manage), as contained in the Qur'an letter As-Sajdah verse 5, the philosophical basis taken is the flow of utilitarianism, which holds the view that the principle of benefit or utility is the most basic moral principle. This research relies on a management theory which explains that management is the accomplishing of a predetermined objectives through the efforts of other people. The approach used in this study is a qualitative naturalistic approach and the method deemed relevant in this study is a qualitative descriptive analysis method, while the data collection technique is triangulation, which uses various combined/simultaneous data collection techniques. The data sources for this study were the head of the MGMP, the head of the madrasa, the teacher of the Qur'an Hadith, and the madrasa supervisor. The conclusion of the study states that MGMP management for improving the professional competence of Al Qur'an Hadith teachers in making scientific papers at State MTs in Majalengka Regency includes planning, organizing, implementing and supervising. MGMP management to improve the professional competence of Al Qur'an Hadith teachers in making scientific writings, is absolutely necessary to be carried out in a focused and focused and sustainable manner so that the competence of Al Qur'an Hadith teachers is more qualified. The recommendation from this study is that the Al-Qur'an Hadith teacher should not feel enough with the abilities he already has, and always develop his competence through various activities and opportunities, innovate and be responsive to various changes.